Characterization of Fusarium wilt in resistant and susceptible gladiolus (Gladiolus spp) genotypes using DNA markers - KUMARI, POONAM; RAO, T MANJUNATHA; SANE, ANURADHA; KUMAR, RAJIV; DHANANJAYA, M V (The Indian Journal of Agricultural Sciences, 2016)
ISSR markers were used for molecular characterization of Fusarium wilt in resistant along with susceptible gladiolus (Gladiolus spp) genotypes namely Arka Amar, Arka Aayush, IIHRG-12 and Pink Friendship to identify markers for screening population for wilt resistance. Twenty nine ISSR primers were screened for the ability to generate reproducible polymorphic bands. Out of 29 primers, 11 primers produced good polymorphism. Among the selected 11 polymorphic primers, 8 primers produced 100 % polymorphism except three primers, viz. 888 (66.67%), 891 (85.71%) and 818 (85.71%). Primer UBC 861 has produced specific band of size 350 bp for both resistant genotypes, viz. Arka Amar and Arka Aayush. UBC Primer 891 primer produced band of size 250 bp for both susceptible genotypes, i.e. Pink Friendship and IIHRG 12. The dendrogram generated using Ward’s method showed that high genetic similarity between genotypes Arka Amar and Pink Friendship at a genetic distance of 8.4. Genotypes Arka Aayush and IIHRG-12 are related to each other at a distance of 8. The results suggest that ISSR markers are useful for detection of resistant bands and also assessing genetic relationship in gladiolus varieties. The identified ISSR marker from the present investigation will help in screening the gladiolus population for Fusarium wilt resistance. Cloning and sequencing the desirable polymorphic DNA fragment converting to SCAR, which can be used as marker for detecting resistance in breeding for Fusarium wilt resistance mechanism in gladiolus.